Pengaruh Kompetensi SDM dan Locus Of Control Pada Pencegahan Fraud dalam Pengelolaan Dana Desa - Dewi, Ni Ketut Putri Pramesti; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 29 No 3 (2019)DO - 10.24843/EJA.2019.v29.i03.p12, 2019)
This research is aimed to acquire the empirical evidence of  the influence of human resource competencies and locus of control on fraud prevention in the management of dana desa. This research has been selecting all of the 27 desa dinas in denpasar as the population. 108 respondent were collected as the sample. One of the non-probability sampling using census to obtained the data. Multiple linear regression technique analysis is applied to analyzing the data. This research shows that human resource competencies and locus of control, have given such an positive impact to the fraud prevention in the vilaage fund management . Keywords : Human Resource Competencies ; Locus Of Control Fraud.